(untitled) (Fiep Bulletin - online, 2015)
The cardiovascular disease is the main cause of death in Brazil and all over the world. The cardiovascular factors of risk are classified as conditionants, cause risks and predisponers. Puffer (2004) define the “athlete’s heart” as a benigne adaptation in virtue of physical activity, presenting diamenters cavities and espessures ventriculars increased. Objective: To verify the incidence of “athlete’s heart” in judo fighters, diferencing the hypertrophic cardiomyopathy (CMH) and to diagnostic cardiovascular diseases. Methods: The sample is constituted of 40 judo fighters between 14 to 24 years that were trained at least 3 years. Submitted to antropometric evaluation, fat percentual, ecodoppler test and questionnaire about the risk factors. These, 28 did evaluation of fat percentual and body mass index (BMI)and 25 answered the questionaire. To statistically analyze, was done the descriptive model of the data. Results: The analyze of the ECO, was done in 40 athletes, resulting in average of 0,1 and standard deviation of +/-1,02. The fat percentual, was done in 28 athlete, and the average was 14,09% and the standard deviation of +/- 9,50.The BMI calculo has presented an average of 24,48 and standard deviation of +/- 5,10. The Chart 2 shows that the 25 athletes who answered the questionnaire, 12 presented conditionants factors, 8 presented predisposes and 3 included conditionants and predisponers. Conclusion From 40 athletes, 4 presented signals of “athlete’s heart”, nothing has presented signals of the CMH and in relation to risk factors, the conditioners factors have presented high. In fat percentual has presented in average to the fight category. In BMI, had normal classified.